Building Resilient Communities through Management Education: A CommunityService Initiative of the Management Study Programfor International Students - Tangkeallo, Dian Intan; Pongtuluran, Althon K.; Tangdialla, Randi; Pundissing, Rati; Matasik, Ade Lisa; Biringkanae, Astriwati; Tiku, Ovita (Jurnal Literasiologi, 2024)
This study aims to explore the impact of management education on building resilient communities through the community service initiative involving international students. The research utilizes a qualitative approach, incorporating a case study design. The study involved interviews with educators, community leaders, and program participants. The main participants included international students participating in the cultural immersion program and members of UKI Toraja who engaged with these students. Participants were selected through purposive sampling, focusing on individuals who were actively involved in the program. Five international students and five members of the Management Study Program at UKI Toraja were chosen to provide a variety of perspectives and experiences, ensuring the study represented diverse viewpoints. In-depth, semi-structured interviews were conducted with the selected international students and UKI Toraja Management Study Program members . The data gathered from interviews and participant observations were transcribed and analyzed through thematic analysis. This approach involved coding the data to uncover recurring themes, patterns, and key narratives related to cultural exchange, learning outcomes, and community impact. The result of this study shows that the impact of management education on building resilient communities through the community service initiative involving international students namely Mutual Learning and Exchange and Increased Social Cohesion.